Alpha-, beta-radioactive aerosols behavior in the ground atmosphere; The Second International Conference on Radiation and Dosimetry in Various Fields of Research, RAD 2014, May 27-30, 2014, Niš, Serbia - Cherepnev M. S. Maksim Sviatoslavovich; Ипполитов И. И. Иван Иванович; Нагорский П. М. Петр Михайлович; Smirnov S. V. Sergey Vasiljevich; Yakovleva V. S. Valentina Stanislavovna; Vukolov A. V. Artem Vladimirovich (2014, 2014)
Title screen